Use of non-governmental maternity services and pregnancy outcomes among undocumented women: a cohort study from Norway - Frode Eick; Odd Martin Vallersnes; Heidi E. Fjeld; Ingvil Krarup Sørbye; Guro Storkås; Marthe Ekrem; Marie Børmer; Sara Andrea Løberg; Cathrine Ebbing; Nanna Voldner; Cecilie Dahl (BMC, 2022)
Abstract Background In 2011 Norway granted undocumented women the right to antenatal care and to give birth at a hospital but did not include them in the general practitioner and reimbursement schemes. As a response to limited access to health care, Non-Governmental Organizations (NGO) have been running health clinics for undocumented migrants in Norway's two largest cities. To further facilitate universal health coverage, there is a need to investigate how pregnant undocumented women use NGO clinics and how this affects their maternal health. We therefore investigated the care received, occurrence of pregnancy-related complications and pregnancy outcomes in women receiving antenatal care at these clinics. Methods In this historic cohort study we included pregnant women aged 18-49 attending urban NGO clinics from 2009 to 2020 and retrieved their medical records from referral hospitals. We compared women based on region of origin using log-binominal regression to estimate relative risk of adverse pregnancy outcomes. Results We identified 582 pregnancies in 500 women during the study period. About half (46.5%) the women sought antenatal care after gestational week 12, and 25.7% after week 22. The women had median 1 (IQR 1-3) antenatal visit at the NGO clinics, which referred 77.7% of the women to public health care. A total of 28.4% of women were referred for induced abortion. In 205 retrieved deliveries in medical records, there was a 45.9% risk for any adverse pregnancy outcome. The risk of stillbirth was 1.0%, preterm birth 10.3%, and emergency caesarean section 19.3%. Conclusion Pregnant undocumented women who use NGO clinics receive substandard antenatal care and have a high risk of adverse pregnancy outcomes despite low occurrence of comorbidities. To achieve universal health coverage, increased attention should be given to the structural vulnerabilities of undocumented women and to ensure that adequate antenatal care is accessible for them.